The effect of 8 weeks taichi chouan training and walking on cardiovascular disease biomarkers in old women’s - Biglari, Niloufar; Arshadi, Sajad; Sadeghian, Mohamadreza (Advances in Nursing & Midwifery, 2017)
Abstract Background and aim: With regard to cardiovascular problems for older people due to lack of movement, The aim of the present study was redirected to an 8-week Tai Chi exercise on cardiovascular disease risk factors, including cholesterol (C), triglycerides (TG), high density lipoprotein (HDL-C), low density lipoprotein (LDL-C) and blood pressure in women elderly. Materials and methods: 30 subjects were selected living in a nursing home in Tehran in two groups randomly: Tai Chi and walking. On the first day and last day blood samples were taken from subjects to measure variables, and were compared between the two groups. Findings: Intragroup and intergroup results showed that both groups can have positive effects on lipid profile but changes in the tai chi group had significantly. Conclusion: Tai Chi had a significant reduction in LDL-C and significant increase in HDL-C, but the Tai Chi group had no significant effect in the levels of cholesterol and triglycerides. Keywords: Cardiovascular Diseases; Hyperlipidemia; Tai Chi